Bad Kitty vs Uncle Murray - Bruel, Nick (Bad Kitty, 2011)
Kitty's owners are taking a week off and leaving Kitty and Puppy at home with Uncle Murray, and it isn't long before Uncle Murray is driven to near madness by shenanigans of epic proportions.